HUBUNGAN OBESITAS DENGAN HIPERTENSI - Purba, Bery Agana; Silitonga, Hendrika A; Sinurat, Suryati (Jurnal Kedokteran Methodist, 2019)
Background : Obesity is a risk factor for hypertension. Based on WHO data in 2016, more than 1.9 billion adults aged 18 years and over are overweight. Of these, more than 650 million adults are obese. In Indonesia, 13.5% of adults aged 18 years and over are overweight, while 28.7% are obese (BMI ≥ 25). Based on WHO data in 2015, it shows that around 1.13 billion people in the world have hypertension. Riskesdas 2018 states that the estimated number of hypertension cases in Indonesia is 63,309,620 people, while the death rate in Indonesia due to hypertension is 427,218 deaths. Objective : To determine the relationship between obesity and hypertension (high blood pressure). Methods : The study was conducted using the literature study method or literature review that focuses on writing results related to the relationship between obesity and hypertension through searches for accredited journal sites such as Google Schoolar, Pubmed, National Library and Research Gate in the 2015-2020 period. Results : Based on several journals that have been reviewed, most journals state that obesity has a significant relationship with hypertension and there are also those who state that obesity does not have a significant relationship with hypertension. Conclusion : There are differences in the results obtained based on several journals that have been reviewed in the discussion of the relationship between obesity and hypertension. This difference in results can be caused by the multifactorial process of hypertension and obesity is one of the causes of hypertension.